1997
DOI: 10.1111/j.1532-5415.1997.tb05975.x
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances of Falls Resulting in Hip Fractures Among Older People

Abstract: Strategies aimed at preventing fall-related hip fractures among the old old and among institutionalized individuals should focus primarily on the modification of intrinsic factors. Modification of environmental hazards has the greatest potential for prevention among the young old and those living in private homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
105
2
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(118 citation statements)
references
References 16 publications
5
105
2
6
Order By: Relevance
“…The National Safety Council reported that in 2001, 15,400 Americans met their death by falling, and of these deaths, the majority (over 80% were people over 65 years of age (National Safety Council, 2002). In terms of the injuries, more than 25% of fall-related injuries in older adults result from slips, and 66% of fall-related hip fractures occur on wet or slippery floor surfaces (Norton, Campbell, Lee-Joe, Robinson, & Butler, 1997). Additionally, falls and hip fractures among older adults rank among the most serious public health problems in the United States, with costs expected to exceed $43.8 billion by the year 2020 (Englander, Hodson, & Terregrossa, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The National Safety Council reported that in 2001, 15,400 Americans met their death by falling, and of these deaths, the majority (over 80% were people over 65 years of age (National Safety Council, 2002). In terms of the injuries, more than 25% of fall-related injuries in older adults result from slips, and 66% of fall-related hip fractures occur on wet or slippery floor surfaces (Norton, Campbell, Lee-Joe, Robinson, & Butler, 1997). Additionally, falls and hip fractures among older adults rank among the most serious public health problems in the United States, with costs expected to exceed $43.8 billion by the year 2020 (Englander, Hodson, & Terregrossa, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…3 In 1 year, 59% of 91 self-reported falls were attributed to trips and slips in 50 independent, communitydwelling older people. 4 Because most falls in older people occur during locomotion, 5 the development of therapeutic interventions to enhance walking and reduce slip propensity is of great clinical importance.…”
mentioning
confidence: 99%
“…The effect of home modifications in preventing falls has been questioned (Norton et al 1997;Sattin et al 1998, Hinman 1998Carter et al 1997), but the Fall STOP project found increased confidence and a reduced fear of falling. Fear of falling has frequently been referred to in the literature as a significant barrier to full independence in the aged (Vellas, Wayne, Romero et al 1997;Lachman, Howland, Tennstedt et al 1998;Mclean & Lord 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 55% of falls occur at home (Tibbitts 1996). They are the most common cause of accidental injury in the elderly requiring hospitalisation (Australian Bureau of Statistics 1996), 85% of fractures involving a fall occur at home, with 25% of these associated with an object in the home (Norton, Campbell, Lee-Joe et al 1997). There has been significant discussion as to the role of intrinsic and extrinsic risk factors (Sattin, Rodriguez, De Vito and Wingo 1998;Hinman 1998) and the need to embrace a multi-factorial approach (Tinetti, Baker & McAvay et al 1994) in reducing falls in the elderly.…”
Section: Introductionmentioning
confidence: 99%